Pengolahan Data Akuntansi Menggunakan ABSS Premier Versi 20 Pada Toko ATK Bekasi - Fahri Bayu Anggoro; Fajar Agustini (LPPM Universitas Bina Sarana Informatika, 2022)
Technology has developed very rapidly in the last few decades so that almost all fields of activity are now using a computerized system, one of which is in the field of accounting. Technological developments have a large enough influence in the business world, resulting in fierce competition that requires companies to be able to keep up with technological developments by utilizing technology such as computers. The financial recording system used by the Bekasi ATK Store is still in the form of manual recording by recording in a folio book, this method can be said to be outdated and prone to errors - errors such as loss of evidence of manual recording, inaccurate reports, not detailed and others. This can cause problems for business actors, because business actors cannot know detailed financial data so they cannot know the development of their business and will also make it difficult to make the right decisions due to lack of financial data. The author feels that the accounting records carried out by the Bekasi ATK Store are less effective and efficient, therefore the author feels that the Bekasi ATK Store needs to use an accounting application program (software) for recording financial data. Keywords: ABSS Premier, Financial Data, Transaction